Cover Picture: Improvement in Aqueous Solubility of Retinoic Acid Receptor (RAR) Agonists by Bending the Molecular Structure (Chem. Asian J. 15/2016). Issue 15 (15th July 2016) - Hiramatsu, Michiaki; Ichikawa, Yuki; Tomoshige, Shusuke; Makishima, Makoto; Muranaka, Atsuya; Uchiyama, Masanobu; Yamaguchi, Takao; Hashimoto, Yuichi; Ishikawa, Minoru
Abstract : Aqueous solubility is a key requirement for many functional molecules. In work featured on the cover, the aqueous solubility of a bioactive compound is improved by a very simple chemical modification strategy, that is, bending the molecule. Changing the substitution pattern of a central aryl ring from para to meta or ortho dramatically enhances the aqueous solubility by up to 890‐fold. The increase of aqueous solubility is attributed to decreased intermolecular interactions in the solid state as a result of the structural changes. The picture shows that bent molecules are more soluble in water than the linear compounds. More information can be found in the Full paper by Minoru Ishikawa et al. onpage 2210 in Issue 15, 2016 (DOI:10.1002/asia.201600744 ).